Perceptions of the Antarctic wilderness: views from emerging adults in Spain and the United States. (24th June 2016) - Peden, John; Tin, Tina; Pertierra, Luis R.; Tejedo, Pablo; Benayas, Javier
ABSTRACT: The preambles of the 1959 Antarctic Treaty and the 1991 Protocol on Environmental Protection to the Antarctic state that Antarctica is to be managed in the interest of all mankind. However, key phrases such as 'interest of all mankind' and 'wilderness and aesthetic values' are subject to interpretation. The objective of this study is to gain a better understanding of public perceptions of the Antarctic wilderness, proceeding from the assumption that public views should be incorporated into the consultative parties' decision making process. The study expands on previous research by exploring whether perceptions of the Antarctic environment varied between students at two comparably sized public universities in Spain and the United States. Four hundred undergraduate students were asked about their values, beliefs and attitudes with respect to environmental management practices in Antarctica. After controlling for course type, responses showed little variation based on nationality. A large proportion of students valued Antarctica as a science laboratory for the benefit of mankind, as one of the world's last great wildernesses, and an important component of the climate system. Students did not support an increase in the number of people going to Antarctica, and favoured limitations on infrastructure development.